Story Telling Using Madihin: Learning Methods for Early Childhood Listening Skills - Eva Eriani; Dimyati Dimyati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2019)
Creativity is the ability to think of something in a new and unusual way then give a unique solution to the problem around us. The role of creativity is increasingly considered very important in the 21st century marked by very fast changes and increasingly complex challenges. So that creativity must be developed early through learning conducted in an integrated manner. This research method is descriptive qualitative with the data source from a classroom teachers and the principal of TK Kanisius Sorowajan on 8th of September 2018. The data collecting procedures are observation, interview and documentation. The data analysis activity included of data reduction, data display, and verification. The results showed that basically, every child was born creative. However, if given stimulus and treatement, the creativity would develop more and more. Creativity development carried out in Kanisius Sorowajan Kindergarten varies by integrating science, art, language, religion and IT learning in developing children's creativity integrally.